1989
DOI: 10.1126/science.2463672
|View full text |Cite
|
Sign up to set email alerts
|

Polymerase Chain Reaction with Single-Sided Specificity: Analysis of T Cell Receptor δ Chain

Abstract: In the polymerase chain reaction (PCR), two specific oligonucleotide primers are used to amplify the sequences between them. However, this technique is not suitable for amplifying genes that encode molecules where the 5' portion of the sequences of interest is not known, such as the T cell receptor (TCR) or immunoglobulins. Because of this limitation, a novel technique, anchored polymerase chain reaction (A-PCR), was devised that requires sequence specificity only on the 3' end of the target fragment. It was u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
274
0
6

Year Published

1994
1994
2004
2004

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 628 publications
(283 citation statements)
references
References 26 publications
3
274
0
6
Order By: Relevance
“…Deletion of nucleotides is probably caused by random exonucleolytic nibbling at the ends of most involved gene segments. 9,[20][21][22][23][24][25][26] Junctional regions are made up of D gene segments, N-region nucleotides, which are randomly inserted by the enzyme terminal deoxynucleotidyl transferase (TdT), 9,10,16,20,21,[23][24][25][26] and P-region nucleotides, ie maximally two palindromic nucleotides in juxtaposition to an untrimmed gene segment. 22 The junctional diversity of the TCRG and TCRD genes has been suggested to compensate for the limited combinatorial diversity of ␥␦ receptors.…”
Section: Introductionmentioning
confidence: 99%
“…Deletion of nucleotides is probably caused by random exonucleolytic nibbling at the ends of most involved gene segments. 9,[20][21][22][23][24][25][26] Junctional regions are made up of D gene segments, N-region nucleotides, which are randomly inserted by the enzyme terminal deoxynucleotidyl transferase (TdT), 9,10,16,20,21,[23][24][25][26] and P-region nucleotides, ie maximally two palindromic nucleotides in juxtaposition to an untrimmed gene segment. 22 The junctional diversity of the TCRG and TCRD genes has been suggested to compensate for the limited combinatorial diversity of ␥␦ receptors.…”
Section: Introductionmentioning
confidence: 99%
“…An anchored polymerase chain reaction (PCR) was performed as previously described. 29 Briefly, liver and kidney poly (A) + RNA was isolated from Balb/c mice using standard procedures. Single strand cDNA was synthesized using Maloney murine leukemia virus reverse transcriptase (Promega, Madison, WI, USA).…”
Section: Genomic Dna Cloningmentioning
confidence: 99%
“…Nucleotide sequence analysis showed that the clone contains a single long open reading frame, but lacked the initiation codon. The remaining coding sequence, along with part of the 5h untranslated region, was obtained by 5h rapid amplification of cDNA ends [20][21][22] (Gibco BRL, Gaithersburg, MD, U.S.A.).…”
Section: Cloning Of Thr Cdna By Differential Display Of Mrnamentioning
confidence: 99%